OLAHRAGA DAN PENGARUH SOSIAL: KAJIAN SOSIOLOGIS PERAN OLAHRAGA DALAM KEHIDUPAN MASYARAKAT INDONESIA - Yan Indra Siregar; Putra Arima; Arya Yuhandika; Yuda Sihotang; Sahrul Akmal; Surya Pasaribu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sport functions not only as a physical activity but also as a social phenomenon that has a broad impact on people's lives. This study aims to analyze the influence of sport on social life through a sociology of sport approach. The discussion covers the role of sport as a social unifier, its positive and negative impacts on community life, and its contribution to national character development. The study uses a literature review method by analyzing various academic sources and related policies. The results show that sport has a unique ability to unite individuals from various social backgrounds, foster positive values ​​such as discipline, sportsmanship, and cooperation, and contribute to economic growth. On the other hand, excessive fanaticism, commercialization, and issues of discrimination are negative impacts that require serious attention. Sports policies are needed that focus on social aspects and character education, not solely on achievement.